2010
DOI: 10.1538/expanim.59.623
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Restriction on the Development of Diabetes and Pancreatitis in Female WBN/Kob-Fatty Rats

Abstract: Abstract:Original WBN/Kob male rats commonly develop chronic pancreatitis by the age of 3 months, while diabetes mellitus occurs at 9 months. In contrast, female rats of this strain do not show pancreatitis or diabetes. The WBN/Kob-fatty rat is a homozygous (fa/fa) congenic strain for the fa allele of the leptin receptor gene (Lepr). In WBN/Kob-fatty rats, both females and males provide a model of non-insulin-dependent diabetes with obesity. The leptin receptor fatty gene (Lepr fa ) induces obesity and hyperph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Excessive caloric intake and consequent obesity cause insulin resistance and impaired pancreatic function (Di Marzo, 2008). Previous reports showed that dietary restriction inhibits the development of diabetes in fa/fa rats by reducing pancreatitis (Akimoto et al, 2010). In our study, however, S. muris infection has not affected the body weight, food and water intake, or the weights of examined organs.…”
Section: Discussioncontrasting
confidence: 69%
“…Excessive caloric intake and consequent obesity cause insulin resistance and impaired pancreatic function (Di Marzo, 2008). Previous reports showed that dietary restriction inhibits the development of diabetes in fa/fa rats by reducing pancreatitis (Akimoto et al, 2010). In our study, however, S. muris infection has not affected the body weight, food and water intake, or the weights of examined organs.…”
Section: Discussioncontrasting
confidence: 69%
“…The fa/fa(WBN/Kob-Lepr fa ) rat, a new congenic strain derived by crossing ZF rats with lean rats, has been claimed to be a new model of T2D with obesity [1,2]. We have elucidated the plasma profiles of glucose, insulin and lipids to further characterize the pathophysiologic features of the fa/ fa rat as a T2D model in comparison with lean (the original WBN/Kob) rats.…”
Section: ± 02 G In Lean Ratsmentioning
confidence: 99%
“…Animal models of T2D are useful to elucidate the pathogenesis of the disease and to evaluate the therapeutic activity of new medications. The currently established rodent T2D models are divided into 2 broad categories: experimentally induced nonspontaneous models, and genetically induced spontaneous models.The WBN/Kob-Lepr fa (fa/fa) rat is a new congenic strain that has been developed by introducing the fa gene of the Zucker fatty (ZF) rat into the original WBN/Kob (lean) rat genome [1,2]. The male, but not female, lean rat is a hereditary model of diabetes mellitus and chronic pancreatitis [13,15].…”
mentioning
confidence: 99%
See 2 more Smart Citations